Jesus - David Flusser; Marina Santorio; Martin Cunz (Brescia Morcelliana, 1997)
Martin Cunz (pref.)
Edizioni San Paolo srl - Piazza Soncino, 5 - 20092 CINISELLO BALSAMO (MI) (non commercial uses only) ® Copyright 2018